THE REDESIGNING STRATEGY OF JEBRES MARKET FOR HERITAGE TOURISM WITH CONTEXTUAL ARCHITECTURAL APPROACH - Yuanita Nur Permata Sari; Ofita Purwani; Hardiyati Hardiyati (Universitas Sebelas Maret Surakarta, 2018)
This paper focuses on the redesign of Jebres Market, Surakarta. The market is redesigned to meet the national standard and to fit the condition in which the nearby Solo Jebres Station Area is changed into heritage tourism area by municipal government. In this case, the market is changed into Tourism Market due to the municipal plan to turn the nearby Solo Jebres Station Area into a heritage tourism area. The plan for the redesign of Jebres Market includes addition of capacity of users, the development of supporting facilities such as parking area, an addition of public area, and also other facilities. As the Solo Jebres Station is a heritage building, the redesign of Jebres Market as the supporting facility for the Station uses contextual architectural approach as mentioned by Brent C. Brolin in Architecture in Context (1980). This is done by adjusting the architectural elements of the architecture of Solo Jebres Station building to be applied to the new Tourism Market. Following Brolin’s theory, the elements applied to the new Market are the proportion of windows, exits and entrances, driveways, building material surfaces, finishing, and textures, parks, and architectural styles in buildings.